Aminopeptidases of germinated and non-germinated barley - Strelec, Ivica (Array, 2009)
Summary: In processes of barley plant development, various endo- and exopeptidases are involved. To determine the type and number of aminopeptidases that could participate in barley seed germination and tissue growth, their activities in extracts of non-germinated and germinated barley (Hordeum vulgare L. cv. Angora) grains and young tissues have been examined, and some of their properties determined. Aminopeptidases (AP) hydrolysing 2-naphthylamides of various amino acids were present in dry and germinated grains, roots, seedlings and leaves, showing preferences for amino acids phenylalanine (Phe), arginine (Arg), leucine (Leu) and methionine (Met), and lower activity towards alanine (Ala), proline (Pro), glycine (Gly) and histidine (His). Levels and ratios of AP activities changed during germination and tissue development, indicating that APs of different specificities are required at different stages of germination and in young tissues. Thus, the increase of all aminopeptidase activities during the first 24 hours of germination and subsequent decrease show significant involvement in seed primary metabolism restoration. The activities of Arg- and HisAP are equally important in green malt. Seedlings and leaves have pronounced substrate specificity for Phe, Leu, Ala and Pro, while roots have the lowest AP specific activities. From the activities and determined properties, the presence of at least six aminopeptidases optimally active at pH=7.4–8.2 could be discerned in dry and germinated grains, and young tissues of Angora barley. Two aminopeptidases are most probably of broad substrate specificity, three show narrow preference with dominating Leu, Phe, or Pro/His, while one is specific for Arg